2015
DOI: 10.14415/konferencijagfs2015.008
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizacija Visoko Plastične Gline Primenom Letećeg Pepela Iz Te Kostolac

Abstract: У раду су приказани резултати лабораторијских испитивања стабилизације глине високе пластичности применом летећег пепела из ТЕ Костолац. Испитан је утицај пепела на однос влажности и суве запреминске тежине, једноаксијалну чврстоћу, CBR, модуле деформабилности и потенцијал бубрења. Добијени резултати су показали да се применом пепела као стабилизатора могу побољшати неке инжењерске карактеристике ове врсте тла. Највеће побољшање је пораст CBR вредности, што ово тло чини употребљивим у путоградњи.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In order to reduce the total railway carbon footprint, the researches of the possibility of fly ash utilisation for the construction of railway embankment are still in progress. Fortunately, the preliminary results of geotechnical laboratory testing showed that investigated fly ash and slag (produced in TPPs in Serbia) could be suitable for utilisation in the railway infrastructure ( Figure 3) [1][2][3][4]. The fly ash from Serbian power plants has pozzolanic properties but, because of low concentration of calcium compounds (less than 10 % CaO), it is devoid of self-cementing characteristics.…”
Section: The Measures To Reduce the Railway Carbon Footprint In Serbiamentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the total railway carbon footprint, the researches of the possibility of fly ash utilisation for the construction of railway embankment are still in progress. Fortunately, the preliminary results of geotechnical laboratory testing showed that investigated fly ash and slag (produced in TPPs in Serbia) could be suitable for utilisation in the railway infrastructure ( Figure 3) [1][2][3][4]. The fly ash from Serbian power plants has pozzolanic properties but, because of low concentration of calcium compounds (less than 10 % CaO), it is devoid of self-cementing characteristics.…”
Section: The Measures To Reduce the Railway Carbon Footprint In Serbiamentioning
confidence: 99%
“…The fly ash from Serbian power plants has pozzolanic properties but, because of low concentration of calcium compounds (less than 10 % CaO), it is devoid of self-cementing characteristics. Because of this it is usually necessary to add binders (such as cement or lime) to fly ash in order to improve its mechanical properties [1,4]. Mechanical properties (CBR, shear strength parameters, compressibility modulus) of all tested samples of fly ash with the addition of binders meet European technical requirements.…”
Section: The Measures To Reduce the Railway Carbon Footprint In Serbiamentioning
confidence: 99%